Nilai Karakter dalam Novel Ingkar Karya Boy Candra - Rizkiya Ananda; Mohd. Harun; Rostina Taib (JIM Pendididikan Bahasa dan Sastra Indonesia, 2021)
The purposee of this research is to (1) know the value of what character is contained in the novel Ingkar by Boy Candra and (2) know the technique of conveying the value of the character in the novel Ingkar by Boy Candra. Thiss study uses a qualitatiive approach. The sourrce of this researrch data is the novel Ingkar by Boy Candra (2020). The research data are parts of The Ingkar novel by Boy Candra that contain character values. Data collection is done by documentation techniques. Data analyss is done qualitatiively by readiing the novel repeatedly, then descriibing or explainiing the value of the characters contaiined in the novel comprehensively. The results showed that (1) there were eleven character values found, namely religious values, tolerance values, hard work values, iindependent values, democratic values, curiosity values, friendly/communicative values, peace-loving values, reading values, and values of responsibility. There are seven character values that are not found, namely the value of discipline, creatiive values, the value of natiional spirit, the valu of love of the homeland, the value of appreciating achievements, the value of environmental care, and the value of social care. The most dominant character values found in this novel are the value of responsibility (2) character value delivery techniques used in this novel there are 5 techniques, namely skiill techniiques, behavior techniques, mind and feling techniques, awareness flow techniques, and other character reaction techniques while the techniques not used in this novel are 4 namely, character reaction techniques, background painting techniques, physical painting techniques, and notes on character identification. The most dominant technique used in this novel is the behavior technique